What Is the Impact of mRNA 5′ TL Heterogeneity on Translational Start Site Selection and the Mammalian Cellular Phenotype? - Curran, Joseph A.; Weiss, Benjamin (Frontiers in Genetics, 2016)
A major determinant in the efficiency of ribosome loading onto mRNAs is the 5’ TL (transcript leader or 5’UTR). In addition, elements within this region also impact on start site selection demonstrating that it can modulate the protein readout at both quantitative and qualitative levels. With the increasing wealth of data generated by the mining of the mammalian transcriptome, it has become evident that a genes 5’ TL is not homogeneous but actually exhibits significant heterogeneity. This arises due to the utilisation of alternative promoters, and is further compounded by significant variability with regards to the precise transcriptional start sites of each (not to mention alternative splicing). Consequently, the transcript for a protein coding gene is not a unique mRNA, but in-fact a complexed quasi-species of variants whose composition may respond to the changing physiological environment of the cell. Here we examine the potential impact of these events with regards to the protein readout.